ASPECTOS FISIOLÓGICOS EM Mangifera indica L. PRODUZIDAS COM REJEITOS DE MINERAÇÃO E TRATADAS COM FERTILIZANTE ORGANOMINERAL - Junior, Romario de Oliveira Silva (2020)
ABSTRACT This work aimed to evaluate the physiological performance, in the field, of two cultivars of Mangifera indica L. ( Palmer and Rosa ) produced on substrates containing 0%, 20% and 50% of mining tailings. During field cultivation, no longer under